STEAM-Based Learning Strategies to Foster Religious and Moral Values Among Young Children - Sefriyanti Sefriyanti; Siti Khomsiyati (Jurnal Pendidikan Anak, 2026)
Developing religious and moral values in early childhood should be fostered through contextual, meaningful learning aligned with children’s developmental characteristics. STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics) is an innovative approach that not only enhances critical thinking and creativity but also fosters children’s religious and moral character from an early age. This study aimed to describe the implementation of STEAM-based learning to develop religious and moral values among children at Tunas Ceria Pilot Early Childhood Education Center. The research employed a qualitative descriptive approach involving one teacher and 15 children aged 5–6 years in Group Gold A. Data were collected through observation, interviews, and documentation, using observation sheets focused on children’s religious and moral development. Data analysis applied the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, and was supported by source and technique triangulation. The findings revealed that STEAM learning was implemented through meaningful play, environmental exploration, collaborative projects, and integrated religious habits. These activities successfully developed gratitude, care for living things, discipline, responsibility, cooperation, empathy, and mutual assistance among children, indicating that STEAM can serve as a holistic and integrative learning strategy in early childhood education